2014
DOI: 10.1016/j.burn.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations when translating “burnout”

Abstract: No study has systematically examined how researchers address cross-cultural adaptation of burnout. We conducted an integrative review to examine how researchers had adapted the instruments to the different contexts. We reviewed the Content Validity Indexing scores for the Maslach Burnout Inventory-Human Services Survey from the 12-country comparative nursing workforce study, RN4CAST. In the integrative review, multiple issues related to translation were found in existing studies. In the cross-cultural instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 70 publications
0
34
0
3
Order By: Relevance
“…The MBI itself has been translated into more than 30 different languages (Maslach et al, ). However, “No study has systematically examined how researchers address cross‐cultural adaptation of burnout” (Squires et al, , p1.). Furthermore, the language used in the MBI has been found to moderate the associations between burnout and its risk factors (Vargas, Cañadas, Aguayo, Fernández, & de la Fuente, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MBI itself has been translated into more than 30 different languages (Maslach et al, ). However, “No study has systematically examined how researchers address cross‐cultural adaptation of burnout” (Squires et al, , p1.). Furthermore, the language used in the MBI has been found to moderate the associations between burnout and its risk factors (Vargas, Cañadas, Aguayo, Fernández, & de la Fuente, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the language used in the MBI has been found to moderate the associations between burnout and its risk factors (Vargas, Cañadas, Aguayo, Fernández, & de la Fuente, ). Squires et al () note that there is a problem in the validity of MBI translations due to cultural understandings of burnout both conceptually and linguistically. This was highlighted by cross‐cultural analysis of the MBI which found that seven of the 22 question items on the MBI received a low kappa score (Squires et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts may lend themselves to improved occupational fulfillment and a sense of well-being with a reduction in the prospect of clinicians encountering stress and burnout 42. Importantly, burnout remains a cross-cultural issue for health professionals 1,2…”
Section: Discussionmentioning
confidence: 99%
“…Both of these instruments have multiple items that can present major conceptual and semantic equivalence problems for translation (Squires et al. , ). Section B focuses on patient safety and quality of care issues.…”
Section: Discussionmentioning
confidence: 99%